Phenol degradation in a fixed-bed bioreactor using micro-cellular polymer-immobilized Pseudomonas syringae - Erhan, E; Yer, E; Akay, G; Keskinler, B; Keskinler, D (Wiley, 2004)
Highly porous (85% void volume) polymer beads with interconnecting micro-pores were prepared for the immobilization of Pseudomonas syringae for the degradation of phenol in a fixed-bed column bioreactor. The internal architecture of this support material (also known as PolyHIPE Polymer) could be controlled through processing before the polymerization stage. The transient and steady state phenol utilization rates were measured as a function of substrate solution flow rate and initial substrate concentration. The spatial concentration of the bacteria on the micro-porous support particles as well as within them was studied using scanning electron microscopy at various time intervals during the continuous operation of the bioreactor. It was found that although bacterial penetration into the porous support was present after 20 days, bacterial viability however, was compromised after 120 days as a result of the formation of a biofilm on the support particles. The steady state phenol utilization at an initial phenol concentration of 200 mg cm(-3) was 100% provided that the flow rate was less than 7 cm(3) min(-1). Substrate inhibition at a constant flow rate of 4.5 cm(3) min(-1) was found to begin at 720 mg dm(-3). The critical dilution rate for bacteria washout was high as a result of the highly hydrophobic nature of the support and the reduction of pore interconnect size due to bacterial growth within the pores in the vicinity of the surface of the support. (C) 2004 Society of Chemical Industry.
Keywords: immobilized Pseudomonas syringae; packed-bed bioreactor; phenol degradation; process intensification; wastewater treatment